On a new genus and twelve new species of jumping spiders from southwestern China (Araneae, Salticidae, Salticinae, Euophryini) - Wang, Weihang; Yu, Ying; Zhang, Junxia (Zootaxa, 2024)
A new genus, Eremitarys gen. nov., and twelve new species of the tribe Euophryini from southwestern China are described: Eremitarys fulva sp. nov., Euochin ailao sp. nov. (♂♀), E. mang sp. nov. (♂), E. memorabilis sp. nov. (♂), E. miao sp. nov. (♂), E. pingbian sp. nov. (♂♀), E. yangtze sp. nov. (♂♀), E. yeyu sp. nov. (♂♀), E. yuan sp. nov. (♂), E. yuxi sp. nov. (♂♀), E. zunyi sp. nov. (♂♀), and Zabka dianmian sp. nov. (♂♀). Diagnostic illustrations and photographs are provided.